2022
DOI: 10.1371/journal.pgph.0001109
|View full text |Cite
|
Sign up to set email alerts
|

What do adolescents think about vaccines? Systematic review of qualitative studies

Abstract: Adolescence presents a key opportunity to build vaccine-related health literacy and promote vaccine confidence and uptake. Although adolescents are central to vaccination programs, their views around vaccines are frequently underrepresented in qualitative literature. We reviewed qualitative studies to systematically identify and summarize existing evidence on adolescents’ own understanding of vaccines and experiences with vaccine decision-making, including self-consent when applicable. CINAHL; Embase; Ovid Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…In the qualitative literature, adolescent perspectives on vaccines have often been missing, overlooking a critical stakeholder group. 13 , 17 Several studies conducted among adolescents have found adolescents are interested in learning more about the HPV vaccine and being involved in the decision-making process. 26–30 In our study, participating students identified several different topics of interest about vaccines, such as managing vaccine-related anxiety, and the benefits of vaccination – all of which could be leveraged to design an effective vaccine educational intervention in SBIPs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the qualitative literature, adolescent perspectives on vaccines have often been missing, overlooking a critical stakeholder group. 13 , 17 Several studies conducted among adolescents have found adolescents are interested in learning more about the HPV vaccine and being involved in the decision-making process. 26–30 In our study, participating students identified several different topics of interest about vaccines, such as managing vaccine-related anxiety, and the benefits of vaccination – all of which could be leveraged to design an effective vaccine educational intervention in SBIPs.…”
Section: Discussionmentioning
confidence: 99%
“…Focus group and interview guides were based on the sensitizing concepts of the study and review of literature examining experiences with SBIPs and HPV vaccination. 13 , 15 , 17 Background information was obtained from consultations with regional health authority medical health officers and nurses responsible for planning grade six vaccine programs, review of relevant documents (SBIP consent forms, vaccine information sheets) and observations of SBIPs days at several nonparticipating schools. We explored the attitudes and perceptions about vaccines in general and HPV vaccination specifically, SBIP, and potential opportunities to increase HPV vaccine uptake.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second strength is that, to the best of our knowledge, no publications have synthesized qualitative research that addresses the issue of the acceptability of HPV vaccines. The selected reviews in this study address barriers [ 47 ], decision-making processes [ 48 , 49 ], interventions [ 50 ], and messages in social networks [ 51 ], among others. Notably, a review was published in 2020 [ 52 ] that analyzed the social aspects related to the acceptance of the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…For example, if people prefer fewer injections, this suggests that the availability of MenABCWY (pentavalent) vaccines may increase vaccine uptake, since they provide the same coverage with two injections instead of three. Qualitative research on this topic is required, particularly to understand the preferences of adolescents who are central to vaccination programs but are frequently underrepresented in qualitative literature [ 10 ]. One previous qualitative study has explored MenACWY vaccine-related knowledge, attitudes, and decision making.…”
Section: Introductionmentioning
confidence: 99%